Social Networks and the Life Course Integrating the Development of Human Lives and Social Relational Networks (Frontiers in Sociology and Social Research,, 2018)
This volume engages the interface between the development of human lives and social relational networks. It focuses on the integration of two subfields of sociology/social science--the life course and social networks. Research practitioners studying social networks typically focus on social structure or social organization, ignoring the complex lives of the people in those networks. At the same time, life course researchers tend to focus on individual lives without necessarily studying the contexts of social relationships in which lives are embedded and "linked" to one another through social networks. These patterns are changing and this book creates an audience of researchers who will better integrate the two subfields. It covers the role of social networks across the life span, from childhood and adolescence, to midlife, through old age.